A new method of subtotal thyroidectomy for Graves' disease leaving a unilateral remnant based on the upper pole. Issue 6 (February 2017) - Liu, Yu; Liu, Bin; Liu, Rui-Lei; Jiang, Hua; Huang, Ze-Nan; Huang, Yong
Abstract: Background: The aim of this prospective randomized study was to evaluate the feasibility of subtotal thyroidectomy with leaving a unilateral remnant based on the upper pole. Methods: Patients who underwent the subtotal thyroidectomy and isthmusectomy leaving either a unilateral remnant based on the upper pole (Group I, 79 patients) or the bilateral dorsal thyroid tissue remained (Group II, 89 patients) were compared in operation time, blood loss, recurrence, and postoperative complications. Results: Among 168 patients analyzed, the operation time remained similar, but the blood loss, the reoperation time, and recurrence in Group I were much less than Group II. In addition, no postoperative hemorrhage occurred in Group I. Two patients (2.28%) in Group II underwent recurrent laryngeal nerve damages. Four patients (5.06%) in Group I and 3 patients (3.37%) in Group II experienced transient hypocalcemia. Recurrence only occurred in Group II. Conclusion: In terms of blood loss, reoperation time, postoperative complication, and the recurrence, subtotal thyroidectomy with recurrent laryngeal nerves identification and the unilateral superior pole remnant of the gland provides a better outcome than subtotal thyroidectomy with bilateral dorsal thyroid tissue remnant.